Cómo se manejan los individuos en las organizaciones según la ética y los procesos humanos de negocio - Navarrete-Zambrano, Cecilia Mercedes (Editorial Grupo AEA, 2022)
Since time immemorial the behavior of the human being becomes a mystery which varies depending on the person and the environment that surrounds him, as the life cycle progresses as eventually all people have the need to find employment to meet the needs through the payment that is given for the services provided to the entity. Within the companies, all collaborators have a responsibility towards society and must behave as responsible entities, in accordance with ethics and respect for people and the environment. The objective of the research is to analyze how individuals are managed within organizations according to the ethics and human processes that exist in each business. This manuscript is based on a literature review methodology with a descriptive and analytical approach to provide an interpretation of the characteristics of the behavior of individuals. The results show that there are still organizations that see their employees as just another resource, without considering their needs as individuals, creating a lack of motivation in the staff at the time of performing their tasks, making necessary the intervention of the human resources department to ensure fair treatment. With this we conclude that the application of ethics is necessary for the success or failure of an entity by representing the ideal standards of conduct for an optimal organizational environment that will bring about efficient processes.